The nature and content of the evaluation of evidence in civil procedure - Atakhanova S.K; Miraliyeva M.K. (Хабаршы. Заң сериясы, 2016)
This article discusses the nature and content of evaluation of evidence in civil procedure. It substantiates the idea that a correct assessment of the evidence by the court is of paramount importance for making a lawful and substantiated decision. In the study of the process of evaluation of evidence is an important question: what it involves, what is its content. In this article there is an attempt to answer the above questions. The article discusses that the comprehensive study of the problems of evaluation of evidence from the point of view of logic, psychological and legal unity achieved the best result. Article sum up the results of the study of legally significant circumstances. Article is devoted to the proceedings to assess the evidence and legal action to assess the evidence.